ОБҐРУНТУВАННЯ КОМПОНЕНТІВ СИСТЕМИ МОРАЛЬНОГО ВИХОВАННЯ МАЙБУТНІХ ОФІЦЕРІВ-ПРИКОРДОННИКІВ (Педагогіка вищої та середньої школи, 2004)
In the article, the author discredits the purposes, components, objects, content of moral bringing up of future officers.